2016
DOI: 10.1177/1947603516654944
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Chondrocyte Implantation to Isolated Patella Cartilage Defects

Abstract: Background. Autologous chondrocyte implantation (ACI) is a durable treatment for patients with chondral defects. This study presents the comprehensive evaluation of patients with patella defects treated with ACI at medium-to long-term follow-up. Methods. Thirty consecutive patients with isolated chondral lesions of the patella were enrolled prospectively. Primary outcome measures were validated patient reported outcome measures and objective magnetic resonance imaging. Results. Nineteen of 30 patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 53 publications
2
51
0
1
Order By: Relevance
“…A total of 84% of patients had good or excellent results after a minimum of 4-year follow-up. Similar results were obtained by von Keudell et al [ 21 ••], showing that 83% of patients had good or excellent functional outcomes after ACI to isolated chondral lesions of the patella with a failure rate of 10% after 15 years of follow-up. As previously mentioned, lateral facet or inferior pole patellar lesions should be addressed with ACI in combination with an anteromedializing TTO to achieve improved outcomes [ 17 , 19 , 67 •].…”
Section: Introductionsupporting
confidence: 87%
“…A total of 84% of patients had good or excellent results after a minimum of 4-year follow-up. Similar results were obtained by von Keudell et al [ 21 ••], showing that 83% of patients had good or excellent functional outcomes after ACI to isolated chondral lesions of the patella with a failure rate of 10% after 15 years of follow-up. As previously mentioned, lateral facet or inferior pole patellar lesions should be addressed with ACI in combination with an anteromedializing TTO to achieve improved outcomes [ 17 , 19 , 67 •].…”
Section: Introductionsupporting
confidence: 87%
“…Associated patellofemoral instability should be addressed with patellar stabilization procedures concomitantly or before the cartilage restoration procedure. 35,46,81,85,89 3.57 96.43…”
Section: Surgical Indicationsmentioning
confidence: 99%
“…76 Several authors later reported comparable results, acknowledging the importance of correcting maltracking before or concurrently with the cartilage procedures. 35,46,81,85,89 Both ACI and OCA were considered valid treatments for large chondral defects in the patella and trochlea except in cases of end-stage osteoarthritis and/or restricted range of motion (<100 -110 ). While end-stage arthritis is a contraindication to cartilage repair, subtotal loss or bipolar lesions without significant joint space narrowing can be treated with ACI or OCA, especially in young patients.…”
Section: Indicationsmentioning
confidence: 99%
“…The AMIC technique showed repair cartilage with poor quality, high rate of incomplete filling (40% to 60%), graft hypertrophy (20% to 40%) and irregular surface and incomplete integration into the border zone (20% to 60%). 44,46 ACI technique had the best quality of cartilage among the cell-based techniques, with a high rate of moderate-to-high defect filling (>50%) in more than a half of patients, complete integration of the graft in more than half of the patients, 15,17,57,61,62 with smooth surface (84% to 91%), 17,62 intact surface without irregularities (58%), 57 high incidence of homogenous structure 17,62 and hypointense or isointense signal. 17,57,62 In addition, a lower rate of graft hypertrophy was seen as compared with other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…56 MRI findings demonstrated high rates of moderate to high defect filling (>50%) in 55% to 100% of patients and graft hypertrophy in 0% to 33% of patients (n = 135 out of 191). 15,17,56,57,61,62 Complete integration to the border zone was found in 47% up to 88% of patients (n = 135 out of 191), 15,17,57,61,62 with 84% to 91% with smooth surface or focal changes (n = 48 out of 91) 17,62 and 58% with intact surface without irregularities (n = 24 out of 31). 57 The structure of the repair tissue was homogeneous in 21% to 58% of patients in 2 studies (n = 58 out of 68) 15,57 and 85% to 95% had more than 50% of homogenous repaired structure in 2 other studies (n = 48 out of 91).…”
Section: Imaging Outcomesmentioning
confidence: 97%